The mission-driven venture : business solutions to the world's most vexing social problems - Lane, Marc J. (Wiley, 2014)
"Practical guidance to maximize financial results while driving positive social changeThe Mission-Driven Venture provides actionable guidance for leveraging the power of the marketplace to solve the world's most vexing social problems. Written by attorney and financial advisor Marc J. Lane, a renowned thought leader and expert on entrepreneurship, social enterprises, impact investing and entrepreneurial finance, this book reaches the full spectrum of interests represented at the intersection of business and social change. Whether a social entrepreneur, impact investor, socially conscious individual, or a nonprofit or foundation leader, any reader committed to social innovation can benefit from this practical roadmap to the rapidly developing arena of social enterprise. Through real-world accounts of the journeys and successes of mission-driven ventures, Lane effectively illustrates the transformative potential of social enterprise, inspiring the reader to be an agent of change. Among the many tools offered through The Mission-Driven Venture, readers will: Find functional guidance to move from idea to reality with a step-by-step guide to designing and implementing a successful mission-driven venture Assess the benefits and challenges of the business models and entity choices available to the social entrepreneur Examine the entrepreneurial linkages between nonprofits and for-profits Recognize governance issues that can arise when mission and profit objectives clash, and discover tools for managing them Explore evolving trends and developments in financing social enterprise Discover methods and tools for measuring and reporting social impact Develop an effective strategy for achieving both financial success and meaningful social impact "--